2011
DOI: 10.1161/strokeaha.110.594671
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Effects of Poststroke Cognitive Impairment No Dementia and Domain-Specific Cognitive Impairments in Nondisabled Ischemic Stroke Patients

Abstract: Background and Purpose-There is some evidence that poststroke dementia, cognitive impairment no dementia (CIND), and mild cognitive impairment predict for poor outcomes such as dementia, death, and institutionalization. However, few studies have examined the prognostic value of CIND, CIND severity, and domain impairments in a poststroke cohort. Methods-A cohort of ischemic stroke patients with baseline cognitive assessments 3 months poststroke were followed up annually for outcomes of dependency, vascular even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 23 publications
5
65
1
9
Order By: Relevance
“…Mild cognitive impairment (MCI; cognitive impairment greater than expected for age in the absence of dementia) [1] is associated with increased risk of dementia in epidemiological studies [2], memory clinic cohorts [3] and in patients with cerebrovascular disease [4,5,6,7]. There is therefore a need for short cognitive screening instruments to identify MCI in clinical practice, trials and large pragmatic studies where lengthy neuropsychological batteries are not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Mild cognitive impairment (MCI; cognitive impairment greater than expected for age in the absence of dementia) [1] is associated with increased risk of dementia in epidemiological studies [2], memory clinic cohorts [3] and in patients with cerebrovascular disease [4,5,6,7]. There is therefore a need for short cognitive screening instruments to identify MCI in clinical practice, trials and large pragmatic studies where lengthy neuropsychological batteries are not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…8 While we aware that many previous study have manage to correlate and compare cognitive disturbance in post stroke patients, we also think that this study is important in our society as quoted from research by Narasimhalu et al which stated that post stroke cognitive impairment could be predictor of post stroke severity and mortality. 9 From the cross-tabulation of the data using MoCA-Ina with cutoff score of 26, we found that 68 subjects (97.14 %) of the sample are diagnosed with post stroke cognitive impairment. The high number percentage somehow comparable with study done by Lestari et al in Jakarta, that found 72.41 % of the post stroke sample subject has cognitive problems regarding other confounding factor such as ischemic stroke risk factor dan ethnic biodiversity of the subjects between these studies.…”
Section: Discussionmentioning
confidence: 90%
“…Over the last few years, more scientists have begun studying this problem, but in clinical practice, addressing post-stroke cognitive impairments has taken a back seat to dealing with motor dysfunctions (Lees, Fearon, Harrison, Broomfield, & Quinn, 2012). Cognitive impairments decrease success in rehabilitation outcomes and disease prognosis; they cause an inability to work and to take care of one's self (Narasimhalu et al 2011;Cumming, Brodtmann, Darby, & Bernhardt, 2014).…”
Section: Introductionmentioning
confidence: 99%